EFEKTIFITAS SISTEM PEMBELAJARAN CYBER BERBASIS APLIKASI GOOGLE MEET UNTUK MAHASISWA PGMI - Mubaidilla, Irfa'i Alfian; Ainiyah, Ziana Dhurrotul; Hidayah, Alfinatul (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
In the current era, lecturers can provide information without having to meet students directly. The most modern situation is the growth of so-called